An overview of the taxation of residential property: is it a good idea? (Public Sector Economics - submission site, 2021)
This article examines the taxation of property in the residential market as a potential revenue-raising tool in public finance. Economists generally consider taxing property to be less distortionary than taxing other tax bases. It ranks well in terms of trade-offs across long-term growth and inequality considerations. Although countries have different societal preferences, recourse to property taxation is not generally widespread. Using panel data methods and stochastic frontier analysis, we provide evidence that government revenue from property taxation is relatively inelastic to house price and quantity developments, and that countries with a higher implicit tax rate tend to be more efficient at collecting the revenue. Despite the increase of prices since 2014, low revenues can be the result of low effective tax rates and outdated house valuation systems.